Chronic Lymphocytic Leukemia Pathobiology, B Cell Receptors, Novel Mutations, Clonal Evolution - Kaur, Prabhjot (Molecular and Translational Medicine,, 2018)
This text provides a comprehensive, state-of-the art review of this field, and will serve as a valuable resource for pathologists and clinical hematologists/oncologists with an interest in chronic lymphocytic leukemia. This book is designed to provide a concise yet comprehensive summary of the traditional and new definitions, prognostic markers, the pathobiology and newer hierarchal classification based on molecular genetics/chromosomal abnormalities. It will include the most up-to-date scientific and clinical information and bring together subject matter that is usually covered separately in various specialties of hematopathology, molecular pathology, basic science and immunology. The book is written in an easy to comprehend format with emphasis on the science and illustrations to explain the same. It is therefore intended to intrigue, the junior resident and the senior pathologists/clinical oncologists and anyone who would like to keep up with this rapidly growing field.